The Limits of Criticism of the Government Under Articles 240 and 241 of Law No. 1 of 2023: Balancing the Protection of State Authority and Civil Liberties - Dila Padila Nurhasanah; Yenik Pujowati; Rully Fildansyah (Westscience Press, 2026)
This study examines the legal limits of criticism directed at the government under Articles 240 and 241 of Law No. 1 of 2023 concerning the Indonesian Criminal Code. The central issue concerns the balance between protecting the authority and institutional integrity of the state and safeguarding freedom of expression as a fundamental civil liberty. This research employs a normative legal method using statutory, conceptual, constitutional, case, comparative, and human-rights approaches. The analysis focuses on the formulation of the offences, the distinction between criticism and insult, the complaint-based nature of prosecution, criminal responsibility for digital dissemination, and the application of the principles of legality, necessity, proportionality, and public interest. The findings indicate that Articles 240 and 241 pursue a legitimate objective insofar as they protect the effective functioning of government and state institutions from serious, malicious, and unlawful attacks. However, the broad and evaluative meaning of terms such as insult, honour, and institutional image creates risks of legal uncertainty, selective enforcement, and a chilling effect on democratic participation. The study finds that criticism should not be criminalized merely because it is harsh, offensive, satirical, emotionally expressed, or damaging to the reputation of a public institution. Criminal liability should arise only where the prosecution proves an objectively unlawful attack, the required intent, the absence of a dominant public-interest purpose, serious and legally cognisable harm, and the inadequacy of less restrictive remedies. Article 241 requires additional safeguards because the dissemination of digital content may occur for purposes of journalism, education, criticism, documentation, or public discussion. The study concludes that Articles 240 and 241 must be interpreted restrictively, with a strong presumption in favour of political expression, to ensure that the protection of state authority does not undermine constitutional democracy and civil liberties.